Perkembangan Tarikat Ahmadiyyah di Negeri Kelantan Darul Naim - Sa'ari, Che Zarrina (Afkar: Jurnal Akidah dan Pemikiran Islam, 2001)
This article attempts to describe the rise and development of sufi order i.e. the Ahmadiyyah Order in Kelantan. It analyses the prominent shaykh of the order who played a vital role to introduce and developed the order among the Malays.